The Influence of Product, Location, and Store Atmosphere on Consumers Repurchase Intention at Sahaya Coffee Shop in Pontianak City - Wiwinda Wiwinda; Neni Triana M (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the influence of product, location, and store atmosphere on repurchase intention among customers of Coffee Shop Sahaya in Pontianak City. The research employed an associative quantitative approach with a total of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression, correlation coefficient, simultaneous F-test, and partial t-test. The regression analysis results indicate the equation Y = 0.218 + 0.234X₁ + 0.378X₂ + 0.339X₃ with a correlation coefficient (R) of 0.776, showing a strong relationship, while the coefficient of determination (R²) is 58.9%, meaning that product, location, and store atmosphere variables affect repurchase intention by 58.9%. The F-test results show that product, location, and store atmosphere simultaneously influence repurchase intention. The partial t-test also indicates that product, location, and store atmosphere have a significant effect on repurchase intention. In conclusion, product, location, and store atmosphere make a real contribution to increasing customers repurchase intention. This study recommends that the management of Coffee Shop Sahaya continue to improve product quality, choose strategic locations, and create a comfortable store atmosphere. Future research is suggested to include additional variables to obtain more comprehensive results.